EDUCATING TEACHERS FOR THE 21st CENTURY USING THE EXAMPLE OF THE JOINT PROGRAMME: "E³: EMPOWERING EDUCATION IN A EUROPEAN CONTEXT" AT THE UNIVERSITY COLLEGE OF TEACHER EDUCATION STYRIA (AUSTRIA) - Kamitz, Katharina (IJRDO- Journal of Educational Research, 2018)
Increased diversity and a growing multicultural environment in today’s classrooms are confronting teachers with new challenges. The requirements for teachers of the 21st century have changed as they are now expected to be global players with international experience and intercultural understanding. The aim of this paper is to discuss different approaches to the question of what a global teacher is and which competences he/she needs and to introduce the joint programme “E³: Empowering Education in a European Context” as an example of good practice.